已知a,b,c,d均为正数,a∧4+b∧4+c∧4+d∧4=4abcd 求证a=b=c=d

来源:学生作业帮助网 编辑:作业帮 时间:2024/08/03 03:20:31
已知a,b,c,d均为正数,a∧4+b∧4+c∧4+d∧4=4abcd 求证a=b=c=d
xQn@~+Rvw^9fv@S!qj<'TQ E-iJo+0ͤ޻%xi\s'm66oVPg}cP2< uפ{0Ŧ~4 궙T~Mj5(aqYl>ky5ֳMY$bl?N j$F O1FrvEd ED0a!!cV$%Z0ש.i,@c8J #;j!Zn 8#:dĢ&C/~-!-:{̧.}ckg]@_;䍎rdfuc٧̶ܭNKU(TYh#pZ }3xtN>:F MqC*{bMCiD

已知a,b,c,d均为正数,a∧4+b∧4+c∧4+d∧4=4abcd 求证a=b=c=d
已知a,b,c,d均为正数,a∧4+b∧4+c∧4+d∧4=4abcd 求证a=b=c=d

 

已知a,b,c,d均为正数,a∧4+b∧4+c∧4+d∧4=4abcd 求证a=b=c=d
因为a^4+b^4+c^4+d^4=4abcd 所以a^4+b^4-2a^2b^2+c^4+d^4-2c^2d^2+2a^2b^2+2c^2d^2-4abcd=0
(a^2-b^2)^2+(c^2-d^2)^2 +2(ab-cd)^2=0
因为(a^2-b^2)^2≥0,(c^2-d^2)^2 ≥0,2(ab-cd)^2≥0
所以a^2-b^2=0,c^2-d^2=0,ab-cd=0
所以(a+b)(a-b)=0,(c+d)(c-d)=0,ab=cd
因为已知a、b、c、d均为正数
所以a=b,c=d a^2=c^2
所以a=b=c=d